2018
DOI: 10.1002/ana.25307
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Thermal Grill Illusion by Spinal Segments

Abstract: ObjectiveA common symptom of neuropathy is the misperception of heat and pain from cold stimuli. Similar cold allodynic sensations can be experimentally induced using the thermal grill illusion (TGI) in humans. It is currently unclear whether this interaction between thermosensory and nociceptive signals depends on spinal or supraspinal integration mechanisms. To address this issue, we developed a noninvasive protocol to assess thermosensory integration across spinal segments.MethodsWe leveraged anatomical kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…When pain is experienced, its intensity is typically mild to moderate (Bouhassira et al, 2005a;Craig and Bushnell, 1994;Leung et al, 2005). However, similar heat and painful percepts can be elicited using different experimental apparatuses, such as alternating cold and warm spiral tubes (Bach et al, 2011;Thunberg, 1896), warm-cold-warm patterns using three thermodes (Kammers et al, 2010;Marotta et al, 2015), or one single cold and one single warm thermode, even at large distances on the skin (Defrin et al, 2008;Fardo et al, 2018). Overall these experiments suggest that the TGI depends primarily upon the spatial pattern of thermal stimulation, while other factors such as the size of the affected area, the number of stimulated afferents, or the distances between component stimuli exert minor influences on the quality and intensity of the illusion (Li et al, 2009).…”
Section: Tgi Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…When pain is experienced, its intensity is typically mild to moderate (Bouhassira et al, 2005a;Craig and Bushnell, 1994;Leung et al, 2005). However, similar heat and painful percepts can be elicited using different experimental apparatuses, such as alternating cold and warm spiral tubes (Bach et al, 2011;Thunberg, 1896), warm-cold-warm patterns using three thermodes (Kammers et al, 2010;Marotta et al, 2015), or one single cold and one single warm thermode, even at large distances on the skin (Defrin et al, 2008;Fardo et al, 2018). Overall these experiments suggest that the TGI depends primarily upon the spatial pattern of thermal stimulation, while other factors such as the size of the affected area, the number of stimulated afferents, or the distances between component stimuli exert minor influences on the quality and intensity of the illusion (Li et al, 2009).…”
Section: Tgi Phenomenamentioning
confidence: 99%
“…Thus, although the generation of TGI percepts is conserved across a variety of spatial configurations, the difference between the cold and warm components does exert a large influence on the perceived thermo-nociceptive quality and intensity of the illusion. TGI phenomena have been investigated using qualitative reports -for example by requiring participants to select from a variety of descriptors relating to the subjective qualities of temperature and pain (e.g., Li et al 2009;Bach et al 2011) -as well as quantitative approaches, such as verbal numerical scales (Scheuren et al, 2014), visual analogue scales (Adam et al, 2014;Craig and Bushnell, 1994;Kern et al, 2008aKern et al, , 2008bLeung et al, 2005) or temperature matching (Fardo et al, 2018;Ferrè et al, 2018;Kammers et al, 2010;Leung et al, 2005;Marotta et al, 2015). From this variety of qualitative and quantitative measures, it emerged that TGI sensations vary from innocuous to painful heat percepts, and can be felt as an intermediate sensation between innocuous and noxious perception (Bach et al, 2011).…”
Section: Tgi Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Though a previous study reported a minor effect of dermatomes during intensity discrimination task on the arm [9], the orientation (spatial relationship) might be calculated differently depending on whether the stimuli are presented within or across dermatomes. It seems that our inwardly and outwardly inclined stimuli were presented to the same degree over two dermatomes (C6 and T1) [10]; however, roll rotation of the arm actually non-uniformly stretches and rotates skin, and this uniformity remains unclear. In addition, the differences in cortical representation of each skin area (i.e., cortical magnification) may be related to the observed distortion on the arm, since the correlation with acuity of shape perception on the finger has been reported [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies could address whether thermo -nociceptive interactions also occur on a larger scale and on both glabrous and hairy skin. Given the different innervation territories and segmental projections of the median and ulnar nerves, one may expect that warmth delivered on the index vs the ring finger might show different interactions with pain delivered on the middle finger (Fardo et al 2018). However, while this hypothesis would predict a significant difference in pain ratings and/or LEPs between our condition 2 (warmth on the index finger) and condition 4 (warmth on the ring finger), we found no evidence for any difference in sensory ratings or LEPs (p > 0.200 in all cases).…”
Section: Discussionmentioning
confidence: 99%